2002
DOI: 10.1046/j.1365-2036.2002.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in the frequency of symptoms and complications of gastro‐oesophageal reflux disease

Abstract: Asian patients in Boston infrequently complain of heartburn, whereas heartburn is commonly reported by both white and black patients. Many patients do not understand the meaning of the term heartburn, however, and so physicians should be cautious when using the term during patient interviews. Complicated gastro-oesophageal reflux disease appears to be predominantly a disorder of whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(118 citation statements)
references
References 24 publications
(25 reference statements)
7
110
1
Order By: Relevance
“…It has been reported that the proportion presenting with reflux as an indication for endoscopy is highest in Whites, followed by Hispanics and then Blacks (Abrams et al, 2008), which is parallel to the incidence order of Barrett's oesophagus and ADC. In addition, evidence suggests that although Whites, Blacks, and Asians report a similar prevalence of heartburn, Whites are more likely to suffer from erosive reflux disease (Spechler et al, 2002;El-Serag et al, 2004;Corley et al, 2007). Finally, it seems that the prevalence of gastro-oesophageal reflux has been increasing in the United States (El-Serag and Sonnenberg, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the proportion presenting with reflux as an indication for endoscopy is highest in Whites, followed by Hispanics and then Blacks (Abrams et al, 2008), which is parallel to the incidence order of Barrett's oesophagus and ADC. In addition, evidence suggests that although Whites, Blacks, and Asians report a similar prevalence of heartburn, Whites are more likely to suffer from erosive reflux disease (Spechler et al, 2002;El-Serag et al, 2004;Corley et al, 2007). Finally, it seems that the prevalence of gastro-oesophageal reflux has been increasing in the United States (El-Serag and Sonnenberg, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The current study confirms what has been demonstrated in prior BE screening studies: that older white males with longstanding GERD are at the highest risk for the development of BE. 16,17 Multiple logistic regression demonstrate that for each year of symptoms, the risk of BE increased by approximately 2%. Of note is that the prevalence of BE in our cohort was high at 22% and much greater than the 5-10% that would be expected in a routine population study.…”
Section: Discussionmentioning
confidence: 99%
“…However, GERD is believed to be less prevalent in Asian countries. Genetic factors, high prevalence of Helicobacter pylori infection, dietary differences, and disparities in parietal cell mass and gastric acid secretion are possible factors that accounted for these racial differences (4). The epidemiological data of GERD from Turkey is scarce, thus, in the present study, we aimed to investigate the prevalence of GERD in a middle Turkey population in relation to demographic features, life-style and health-seeking behaviors of patients.…”
Section: Introductionmentioning
confidence: 99%